Fluoxetine-induced perinatal morbidity in a sheep model - Domingues, Rafael R.; Beard, Adam D.; Connelly, Meghan K.; Wiltbank, Milo C.; Hernandez, Laura L. (Frontiers in Medicine, 2022)
Selective serotonin reuptake inhibitors (SSRI) are the most common antidepressants used by pregnant women. However, adverse pregnancy outcomes have been described in women taking SSRI during pregnancy – placental lesions, premature birth, poor neonatal adaptation. We aimed to investigate the effects of fluoxetine (Prozac; most commonly used SSRI) treatment during the last month of gestation on pregnancy complications, placental and neonatal health in a non-depressed sheep model. On day 119 ± 1 postbreeding (experimental day 0; E0) of a 151-day expected gestation, Hampshire ewes were randomly assigned to receive fluoxetine (n = 9 ewes, 15 lambs; daily intravenously treatment with 10 mg/kg on E0 and E1 and 5 mg/kg daily thereafter until parturition) or to a control group (n = 10; 14 lambs; vehicle only). Blood samples from ewes were collected throughout the experimental period and postpartum; blood from lambs were collected postpartum. Analysis of variance was used for statistical analysis. Fluoxetine treatment reduced placentome growth during the last month of pregnancy. Gestation length was decreased by 4.5 days in fluoxetine-treated ewes. Birthweight was reduced in lambs exposed to fluoxetine in utero; weights remained decreased until postnatal day 3. Placentome diameter by birthweight ratio was not different between groups suggesting that the decreased placentome diameter was accompanied by decreased lamb birthweight. During the first week postnatal, lambs exposed to fluoxetine in utero had decreased blood pH and decreased total carbon dioxide, bicarbonate, and base excess and increased lactate (days 3 to 6), collectively indicative of metabolic acidemia. Additionally, ionized calcium was decreased between postnatal days 0 to 4 in lambs exposed to fluoxetine in utero. Using a non-depressed animal model clearly defines a role for SSRI on the occurrence of perinatal complications and neonatal morbidity. The decreased placentome diameter, shortened gestation, decreased birthweight, decreased calcium levels, and neonatal acidemia suggest the occurrence of intrauterine growth restriction. The persistence of neonatal acidemia for several days postpartum suggests poor neonatal adaptation to extrauterine environment.